2008
DOI: 10.1017/s146342360800073x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based primary health care and local research: a necessary but problematic partnership

Abstract: Background: Front-line NHS staff undertake small research projects to answer questions about local patients and services, but these projects often face considerable challenges. This paper reports on one such project. Aims and methods of study:The study used structured interviews in order to find out about the knowledge of nutrition among Bangladeshis using an NHS Walk-in Centre. Development of the study: Time constraints posed considerable difficulties in progressing and completing the study; flaws in the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Research findings from some time ago may thus be unhelpful in supporting health promotion initiatives. For example, Abbott et al 27 found that earlier evidence of strong/weak as a key category in how Bangladeshis think about food had lost its salience less than 10 years later. More generally, significant improvements in general health in second generation compared with first generation Bangladeshis have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Research findings from some time ago may thus be unhelpful in supporting health promotion initiatives. For example, Abbott et al 27 found that earlier evidence of strong/weak as a key category in how Bangladeshis think about food had lost its salience less than 10 years later. More generally, significant improvements in general health in second generation compared with first generation Bangladeshis have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Such challenges and study limitations have been reported elsewhere (eg, Abbott et al ., 2008). They mean that the role of such collaborative studies is to generate ‘locally useful’ information that compliments rather than replaces evidence that is generated by studies which are based on more rigorous research designs.…”
Section: Discussionmentioning
confidence: 99%